How to bag a geek. (Economist, 2015)
The article focuses on the demand for software developers and engineers in the U.S. in 2015. Topics include the employment rate among technology industry workers, the competition between firms for software development talent, and how dependent software-based firms are on their employees. Information is provided on the underrepresentation of women in the technology industry.